2022
DOI: 10.3390/ijerph19169854
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of My Jump 2 Derived from Crouching and Standing Observation Heights

Abstract: The crouching or prone-on-the-ground observation heights suggested by the My Jump app are not practical in some settings, so users usually hold smartphones in a standing posture. This study aimed to analyze the reliability of My Jump 2 from the standardized and standing positions. Two identical smartphones recorded 195 countermovement jump executions from 39 active adult athletes at heights 30 and 90 cm, which were randomly assessed by three experienced observers. The between-observer reliability was high for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
1
9
0
1
Order By: Relevance
“…The mean differences for jump height, flight time, and peak power were only 0.18 cm, 1.59 ms, and 9.76 w, respectively, showing no significant differences for these variables. The Bland-Altman plot also revealed mean differences inter-observers for jump height similar to studies conducted on a rigid surface ( Balsalobre-Fernández, Glaister & Lockey, 2015 ; Jimenez-Olmedo et al, 2022 ). However, it is noteworthy that a larger limit of agreement was found.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The mean differences for jump height, flight time, and peak power were only 0.18 cm, 1.59 ms, and 9.76 w, respectively, showing no significant differences for these variables. The Bland-Altman plot also revealed mean differences inter-observers for jump height similar to studies conducted on a rigid surface ( Balsalobre-Fernández, Glaister & Lockey, 2015 ; Jimenez-Olmedo et al, 2022 ). However, it is noteworthy that a larger limit of agreement was found.…”
Section: Discussionsupporting
confidence: 68%
“…Also, different types of jumps and variables were investigated, including squat jumps, CMJ, drop jumps, flight time, jump height, and asymmetry index ( Haynes et al, 2019 ). Although the My Jump2 ® app consistently presented excellent values of reliability and validity when compared to force platforms and jump mats ( e.g ., Cruvinel-Cabral et al, 2018b ; Jimenez-Olmedo et al, 2022 ; Rago et al, 2018 ; Soler-Lopez et al, 2022 ), to date it was not found any scientific investigation that had tested the validity and reliability of the My Jump2 ® app to measuring jump height in sand surface. Furthermore, validity and reliability studies had focus in investigate males ( Carlos et al, 2015 ; Thomas et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the height of the smartphone above the ground was not specified. In fact, it has been demonstrated that there is no significant difference in the results obtained from measurements taken at different heights above the ground when tested using the My jump2 app ( 33 ). Therefore, if a tripod is not available in a realistic measurement environment, it is feasible for the evaluator to conduct the test with a mobile phone in hand.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of both technologies is usually limited to research or high-performance centers due to their high cost. Because of these high prices and given the demand by specialists to have tools that allow them to determine the vertical jump, numerous instruments have proliferated, which are more manageable and cheaper and which allow estimating the vertical jump in all types of populations and situations [10]. All these new instruments, such as accelerometers, jump 2 of 13 mats, or tailored video-based systems are more affordable alternatives than force platforms and motion capture systems.…”
Section: Introductionmentioning
confidence: 99%